Management of deep breathing relaxation to reduce pain in Bartholin cyst patients: Scoping Review - Darmi Arda; Nur Andani (Edukasi Ilmiah Indonesia, 2025)
Introduction: Bartholin cysts are common in women of reproductive age and may cause significant pain, particularly when infection or abscess formation occurs. Pain management is typically approached through pharmacological and surgical interventions. However, non-pharmacological methods such as deep breathing relaxation (DBR) have emerged as promising complementary strategies. This scoping review aims to identify and map the scientific evidence related to the application of deep breathing relaxation techniques for pain management in patients with Bartholin cysts.. Methods: The review followed the Arksey and O’Malley framework. A comprehensive search was conducted across PubMed, Scopus, CINAHL, Cochrane Library, and Google Scholar using keywords including “Bartholin cyst,” “deep breathing,” and “pain management.” Eligible studies were screened and analyzed descriptively. Results: A total of 11 studies met the inclusion criteria, encompassing randomized controlled trials, quasi-experimental designs, and observational studies. Most studies reported that DBR techniques such as diaphragmatic and paced breathing effectively reduced pain intensity, enhanced patient comfort, and decreased anxiety prior to procedures for Bartholin cyst treatment. Conclusions: Deep breathing relaxation techniques represent a promising non-pharmacological approach for managing pain in Bartholin cyst patients. These methods are simple, non-invasive, and capable of improving the overall care experience. Further high-quality studies are needed to strengthen the evidence base for their effectiveness in this specific clinical context